I, KKK the autobiography of a historian - Khoo, Kay Kim 1937-2019; Khoo, Eddin (Kala Publishers Sdn. Bhd., 2017)
I, KKK - The Autobiography of a Historian recounts the life of Emeritus Prof. Tan Sri Dato' Dr. Khoo Kay Kim - from his earliest memories in a time of war and conflict, all through his journey into academic life in post-independence Malaysia. Prof. Khoo's quaint recollections paint an intimate picture of life in a fledgling country finding its own unique sense of 'nationhood', laced with his sharp observations as one of the country's most celebrated academics.